The Processes of Institutionalization and Deinstitutionalization of Political Science in Central Asia on the Example of Kazakhstan, Tajikistan and Uzbekistan - Taisheva, V.V. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2017)
Political science is a relatively new science in Central Asian countries. The formation of the science began at the end of the 20th century. Based on Central Asian republics’ practice of state building and cultural and value heritage, a certain scientific and theoretical basis of political science has been developed over the past period. In addition, an institutional structure has been created that allows conducting research and analytical activities in the sphere of politics. However, despite initial successes in the process of institutionalization, in the countries of Central Asia political science still needs to develop and resolve existing problems.